2013
DOI: 10.5137/1019-5149.jtn.8541-13.1
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effect of magnesium sulfate and dexamethasone on intrauterine ischemia in the fetal rat brain: ultrastructural evaluation

Abstract: AIm:The aim of this study was to investigate the neuroprotective effect of magnesium sulfate and dexamethasone on oxidative damage in intrauterine ischemia. mAteRIAl and methods:In this study, 19-day pregnant rats were divided into five groups. Fetal brain ischemia was achieved in the ischemia/ reperfusion (I/R) group by bilaterally closing the utero-ovarian artery with aneurysm clips for 30 min and subsequently removing the aneurysm clips for 60 min for reperfusion. Mg (600 mg/kg) and dexamethasone (0.25 mg/k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 19 publications
0
6
0
3
Order By: Relevance
“…Coronal sections (50–150 μ m) were cut with a vibratome (UC7; Leica EM, Solms, Germany). Sections were used to observe dopaminergic neuron morphology under a transmission electron microscope (H‐7650, Hitachi, Troy, MI, USA) as previously described …”
Section: Methodsmentioning
confidence: 99%
“…Coronal sections (50–150 μ m) were cut with a vibratome (UC7; Leica EM, Solms, Germany). Sections were used to observe dopaminergic neuron morphology under a transmission electron microscope (H‐7650, Hitachi, Troy, MI, USA) as previously described …”
Section: Methodsmentioning
confidence: 99%
“…These drugs inhibit the synthesis of almost all known cytokines and cell surface molecules required for immune function and suppress the activity of nuclear factor kappa B (NF‐κB) . Several reports have recently demonstrated that systemic corticosteroid administration might have a protective effect against I/R injury in several organs, including the liver, kidney and brain, via through the immunosuppressive functions of corticosteroid . Based on these findings, we speculate that the application of corticosteroid would protect against the development of a PU after cutaneous I/R in mice.…”
Section: Introductionmentioning
confidence: 74%
“…Prevented ↑ lipid peroxidation induced by ischemia 30 min after reperfusion. (continued on next page) reduced lipid peroxidation and mitochondrial damage induced by transient occlusion of utero-ovarian arteries 60 min after reperfusion (Hasturk et al, 2013). Overall, such studies suggest that maternal MgSO4 treatment may act through distinct mechanisms, especially by inhibiting oxidative stress, and could also be used to prevent HI damage in addition to being an efficient prophylactic therapy for infants at risk of prematurity.…”
Section: Male and Femalementioning
confidence: 93%
“…MgSO 4 , used as a preventive treatment, has anti‐oxidant properties in a model of maternal hypoxia by reducing free radicals overproduction in term fetuses brains of guinea pigs (Maulik et al, 1999), and decreases lipid peroxidation 30 min after reperfusion following bilateral occlusion of utero‐ovarian arteries in rats (Solaroglu et al, 2011). In a similar model, maternal MgSO 4 treatment associated to dexamethasone reduced lipid peroxidation and mitochondrial damage induced by transient occlusion of utero‐ovarian arteries 60 min after reperfusion (Hasturk et al, 2013). Overall, such studies suggest that maternal MgSO4 treatment may act through distinct mechanisms, especially by inhibiting oxidative stress, and could also be used to prevent HI damage in addition to being an efficient prophylactic therapy for infants at risk of prematurity.…”
Section: Pharmacological Agentsmentioning
confidence: 99%